Jury Commissioner Carl Hernandez's Retirement Dinner at Fresno County Plaza Ballroom - Watkins, Howard::::::::: (1988)
Carl Hernandez speaking at lectern with Fred Yamamoto and Judges Mario Olmos and Robert Mardikian seated